The Development of Aquatic Learning Model in Elementary School Through Traditional Game Lit-litan - Hendrayuda, Viktor; Rahayu, Tandiyo; Setyawati, Heny (Journal of Physical Education and Sports, 2019)
This research aims to generate aquatic learning model through traditional game Lit-litan in Elementary School.  This research is a type of Research and Development (R&D). The subjects of research are 2nd grade students of SD Negeri Bulu Lor Semarang City. The research instrument is questionnaire to find out student ability in cognitive aspect, affective aspect, and psychomotor aspect. Based on the result of big scale trial for cognitive aspect ability, 64 students or 89.19% are included in very good category, 10 students or 13.51% are included in good category.  In addition, from the result of affective aspect, 66 students or 89.19% are included in very good category, 7 students or 9.45% are included in good category, and 1 student or 1.35% is included in good enough category.   Whereas in psychomotor aspect, 59 students or 79.73% are included in very good category, 8 students or 10.81% are included in good category, 5 students or 6.776% are included in good enough category, and 2 students or 2.70% are included in less good category.  Based on research result on frequency distribution in cognitive aspect, affective aspect and psychomotor aspect, it can be concluded that from 74 students: for cognitive aspect, students with mean of 89.59% are included in very good category, for affective aspect, 89.5% are included in very good category, whereas for psychomotor aspect, 83.24% are included in very good category. The use of traditional game Lit-litan can increase pulse, the pulse increase before activity showed mean of 83.56 whereas after activity has mean of 127.52. The conclusion which is related to product use is that physical education, sports and health can use aquatic learning model in Elementary School through traditional game Lit-litan as alternative for learning and introduce traditional game to students.